Environmental Accounting Disclosure on Firm Value (Study of Manufacturing Companies Listed on The Indonesian Stock Exchange 2017-2020) - Nugraha, Arie Apriadi; Putra, Sugih Sutrisno; Muhammad, Rahma Nazila; Bukhori, Eka Panca; Al-Gholy, Afky; Junaedi, Rendi (PT Larva Wijaya Penerbit, 2024)
Increasing the value of the company needs to be done so that the company's internal and external parties can improve their environmental performance through appropriate environmental accounting disclosures. This study aims to obtain empirical evidence regarding the effect of environmental accounting disclosures and environmental performance on firm value in the manufacturing sector listed on the Indonesia Stock Exchange (IDX) for the 2017-2020 period. This study uses a sample of 43 manufacturing companies in Indonesia where the data needed in this study is in the form of financial report data obtained from the Indonesian Stock Exchange Gallery. The sampling method is purposive sampling. The data analysis technique used is single linear regression using SPSS. The results showed that the environmental accounting disclosure variable had a significant effect on firm value. Meanwhile, the environmental performance variable has no effect and is not significant on firm value. The single linear regression model in this study has an R2 value of 77.48%, which means the firm value can be explained by using the variable value of environmental accounting disclosures, where the remaining 22.52% is influenced by other factors, variables outside the model that have been studied.